2010
DOI: 10.1128/iai.01293-09
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a Model Host for Candida albicans Infection

Abstract: In this work, the zebrafish model organism was developed to obtain a minivertebrate host system for a Candida albicans infection study. We demonstrated that C. albicans can colonize and invade zebrafish at multiple anatomical sites and kill the fish in a dose-dependent manner. Inside zebrafish, we monitored the progression of the C. albicans yeast-to-hypha transition by tracking morphogenesis, and we monitored the corresponding gene expression of the pathogen and the early host immune response. We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
88
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 49 publications
2
88
0
Order By: Relevance
“…They found that the C. albicans induced mortalities among adult zebrafish in a dose-dependent manner. Moreover, histopathological findings revealed that C. albicans colonized multiple anatomical sites in the adult zebrafish (Chao et al, 2010). Epithelial cells play an important role in signaling specific cells to support an immune response to C. albicans (Gratacap et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the C. albicans induced mortalities among adult zebrafish in a dose-dependent manner. Moreover, histopathological findings revealed that C. albicans colonized multiple anatomical sites in the adult zebrafish (Chao et al, 2010). Epithelial cells play an important role in signaling specific cells to support an immune response to C. albicans (Gratacap et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It also acts as a source of human infection (Calderone, 2002). Chao et al, 2010 assessed the use of zebrafish as a host model to study the pathogenicity of invasive C. albicans. They found that the C. albicans induced mortalities among adult zebrafish in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…rected gene knockdown, both of which are techniques available with the larval host (19). Also, while others have described a localized embryonic zebrafish infection model (19), it is not clear if and how these infections parallel human diseases of clinical importance, such as disseminated candidiasis.…”
mentioning
confidence: 99%
“…The embryonic zebrafish (Danio rerio) has a number of advantages as a model that makes it an increasingly attractive vertebrate host in which to study infectious disease (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The zebrafish is genetically tractable with a sequenced genome (http://www.sanger.ac.uk/Projects/D_rerio/) and is amenable to forward and reverse genetic screens.…”
mentioning
confidence: 99%